2005
DOI: 10.1158/1078-0432.ccr-05-0182
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Inhibit Cell Death in Ovarian Cancer and Up-regulate Caspase Inhibitor cIAP2

Abstract: Purpose: Almost all patients with epithelial ovarian cancer receive chemotherapy and, concurrently, the synthetic steroid hormone dexamethasone to alleviate the side effects. This study aims to test the impact of steroid hormones on the apoptosis of epithelial ovarian cancer cells and to identify its mediators. Experimental Design: Tumor cell lines from 19 patients with advanced epithelial ovarian cancer were analyzed for glucocorticoid receptor, estrogen receptor, progesterone receptor, and androgen receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…Resistance to apoptosis accompanied by uncontrollable cell division could promote growth of tumor mass in the nude mice. This working model is also supported by the knowledge that a G 2 /M checkpoint defect promotes tumorigenesis (3) and that there is close association of up-regulation of three such antiapoptotic proteins, Bcl-xL, XIAP, and cIAP2, with constitutive activation of NF-B and resistance to apoptosis in a variety of human malignancies (45)(46)(47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 82%
“…Resistance to apoptosis accompanied by uncontrollable cell division could promote growth of tumor mass in the nude mice. This working model is also supported by the knowledge that a G 2 /M checkpoint defect promotes tumorigenesis (3) and that there is close association of up-regulation of three such antiapoptotic proteins, Bcl-xL, XIAP, and cIAP2, with constitutive activation of NF-B and resistance to apoptosis in a variety of human malignancies (45)(46)(47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 82%
“…Recently, more and more data from preclinical studies, and to some extent from clinical studies, have strongly recommended a GC-conferred resistance to cancer therapy in the majority of malignant solid tumors -irrespective of tumor origin and the nature of specific anticancer drugs (Wolff et al 1996, Weller et al 1997, Webster et al 2002, Herr et al 2003, Wu et al 2004, Gassler et al 2005, Runnebaum & Brüning 2005, Sui et al 2006, Zhang et al 2006a,b,c,d,e, 2007. In this study, we have demonstrated that Dex could protect human ovarian IgG (10 µg/ml) Anti-β1 (µg/ml) Figure 4 Dex-enhanced cell attachment and cell survival are partially reversed by integrin b1-blocking antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that GC-conferred cellular resistance to cancer therapy may occur through multiple mechanisms, for example, by enhancing DNA repair capacity, suppressing host anti-tumor immune responses, and blocking apoptosis (Rutz 2002, Herr et al 2003, Rutz & Herr 2004. Some dexamethasone (Dex)-induced proteins, such as the inhibitors of apoptosis (cIAP-2, X-IAP, Bcl-XL, and Bcl-2), mitogen-activated protein kinase phosphatase-1, as well as GC-induced serum, and GC-inducible kinase-1 (SGK-1) may contribute to the prevention of chemotherapy-induced apoptosis by GCs (Webster et al 2002, Herr et al 2003, Wu et al 2004, Runnebaum & Brüning 2005). However, the molecular mechanisms underlying the anti-apoptotic effect of GCs in epithelial cells are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…GCs are known inducers of apoptosis in numerous cell types, including thymocytes, eosinophils, neutrophils, hippocampal neurons, and proliferative chondrocytes (56 -60), and various malignancies of lymphoid origin and thus have become one of the most common therapeutic agents for leukemias and lymphomas (61). Interestingly, GCs have been described to exert an anti-apoptotic effect on epithelial ovarian or breast cancer cells, human glioblastoma, hepatoma, and fibroblasts (62)(63)(64)(65)(66). The antiapoptotic effect of GCs on keratinocytes is achieved through the concerted suppression of pro-apoptotic and induction of anti-apoptotic genes.…”
Section: Of Gc-regulated Genesmentioning
confidence: 99%